2018
DOI: 10.1039/c7ee03432f
|View full text |Cite|
|
Sign up to set email alerts
|

Universal kinetic solvent effects in acid-catalyzed reactions of biomass-derived oxygenates

Abstract: Experiments and molecular simulations are combined to understand organic solvent effects, enabling prediction of acid-catalyzed reaction rates for biomass conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 75 publications
4
149
0
Order By: Relevance
“…[22][23][24] GVL has thus been considered as one of the most important platform chemicals available in future lignocellulosic biorefineries. GVL possesses excellent solvent properties (e.g., solvation) for homogeneous and heterogeneous catalysis, [25][26][27][28][29][30][31][32][33][34][35] but it may also serve as stable and non-toxic platform chemical to be converted to a wide range of other useful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] GVL has thus been considered as one of the most important platform chemicals available in future lignocellulosic biorefineries. GVL possesses excellent solvent properties (e.g., solvation) for homogeneous and heterogeneous catalysis, [25][26][27][28][29][30][31][32][33][34][35] but it may also serve as stable and non-toxic platform chemical to be converted to a wide range of other useful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work of BAS catalyzed dehydration and hydrolysis reactions studied how the energetics of proton transfer to reactants with varying hydroxyl groups densities (hydrophilicity) is affected by the composition of organic solvents mixed with water. Organic co-solvents caused water-enriched domains to form in the vicinity of reactant hydroxyl groups, increasing hydroxyl group hydrogen-bonding strength with neighboring water molecules, and leading to stabilized proton transfer and protonated transition states compared to pure water 41 . An exhaustive study of mixtures of water with either DMSO, dioxane, THF, GVL, or acetonitrile demonstrated that molecular-scale interactions form multicomponent solvent clusters with highly varying proton affinities compared to either pure component.…”
Section: Resultsmentioning
confidence: 99%
“…Based our findings and previous research, at entative mechanism is proposed for the dehydration of fructose to HMF catalyzed by PVP@[SO 3 H] 0.17 -SO 3 H( Figure S24). [16] To examine the stability as well as recyclability of the catalytic material, PVP@[SO 3 H] 0.17 -COF was used as ac atalyst up to five times.A sd epicted in Figure S25, HMF was obtained in 97.1 %yield even after five runs and no significant loss of activity was observed. Ah ot filtration test revealed that the obtained activity is not related to any leaching of the catalytically active acid sites (no remaining activity in the supernatant).…”
Section: Angewandte Chemiementioning
confidence: 99%